THE DIRECTION OF TERENGGANU TOURISM INDUSTRY IN SUSTAINING BUSINESS GROWTH: AN UNDERLYING FRAMEWORK - Wan Abd Aziz, Wan Mohd Amin; Muhammad Abi Sofian, Abd. Halim; Shaladdin, Muda; Ahmad Munir, Mohd Salleh (2013)
Business sustainability is recognized as a crucial catalyst to the industrial direction and business growth in any industry. This paper focuses on the Terengganu tourism industry efforts to create long term business sustainability through higher profitability, effective management, business performance, and competitive advantage. The state of Terengganu in the East-Coast of Peninsular Malaysia is strategically located as a tourist destination. Therefore, the state tourism board needs to inculcate the right direction of its tourism industry among its tourism agencies and service providers. We argue that establishing the direction of tourism industry is critical in sustaining the business growth. To this end, numerous factors have to be considered in developing the industrial direction of the Terengganu tourism industry which includes heritage sustaining and development, the promotion of Terengganu heritage, the tourism product development, and human resources in tourism industry. This conceptual paper provides scholars and practitioner using underlying framework from the previous literature study regarding the direction in sustaining the business growth in Terengganu tourism industry.